Pengaruh Kepercayaan Dan Kemudahan Terhadap Keputusan Belanja Online (Studi Pada Pengguna Tokopedia) - TRI LESTARI, INDAH; WIDYASTUTI (Jurnal Ilmu Manajemen (JIM), 2019)
The development of e-commerce in Indonesian has made changes in the pattern of public spending which is increasingly shifting towards electronics or online shopping. This change in shopping behavior patterns is indicated by increasing sales. Companies certainly need to build trust and must provide convenience in the use of consumer spending decisions. This study aims to analyze and discuss the effect of trust and ease of use on online shopping decisions (studies on Tokopedia users). In this study the population is Tokopedia users aged 19-34 years who have shopped at least twice in the past three months. And the sample used was 110 respondents with an online questionnaire distribution system. The method of determining the sample in this study is nonprobability sampling and the sampling technique using judgmental sampling. The technique of data collection used in this study is the questionnaire analyzed using a Likert scale. This type of research is quantitative with the data analysis technique used is multiple linear regression analysis with SPSS version 18. The results of this study indicate that there is a significant effect of trust and ease on online shopping decisions. Keywords: e-commerce; ease; online shopping decisions; tokopedia; trust.